Evaluation of Nature Inspired Metaheuristics for Search and Reconnaissance Operations by Rotary-wing Aircrafts - Yokoyama, André; Mury, Antonio; Ferro, Mariza; Schulze, Bruno (Anais do Brazilian e-Science Workshop (BreSci), 2017)
The main objective of this work is the evaluation of two nature inspired meta-heuristics, Genetic Algorithms and Ant Colony, for the development of an application that can generate optimized routes for aircraft, attending the requirements of the Brazilian Navy. This work presents the methods developed, complying with two main constraints: checkpoints mobility and limited aircraft autonomy. It also presents the results of tests performed with the methods developed and an evaluation of their performances.